Aspect based sentiment analysis of movie reviews: Finding the polarity directing aspects - Parkhe V.; Biswas B. (My University, 2025)
Sentiment analysis of a movie review plays an important role in understanding the sentiment conveyed by the user towards the movie. In the current work we focus on aspect based sentiment analysis of movie reviews in order to find out the aspect specific driving factors. These factors are the score given to various movie aspects and generally aspects with high driving factors direct the polarity of the review the most. The experiment showed that by giving high driving factors to Movie, Acting and Plot aspects of a movie, we obtained the highest accuracy in the analysis of movie reviews. © 2014 IEEE.